The fundamental group of the space of maps from a surface into the projective plane - Gonçalves, Daciberg L.; Spreafico, Mauro (MATHEMATICA SCANDINAVICA, 2009)
In this work we compute the fundamental group of each connected component of the function space of maps from a closed surface into the projective space